2020
DOI: 10.1002/ajmg.a.61776
|View full text |Cite
|
Sign up to set email alerts
|

Leukoencephalopathy in Al‐Raqad syndrome: Expanding the clinical and neuroimaging features caused by a biallelic novel missense variant in DCPS

Abstract: Al‐Raqad syndrome (ARS) is a rare autosomal recessive congenital disorder, associated mainly with developmental delay, and intellectual disability. This syndrome is caused by mutations in DCPS, encoding scavenger mRNA decapping enzyme, which plays a role in the 3‐prime‐end mRNA decay pathway. Whole‐exome sequencing was performed on an offspring of a consanguineous family presenting with developmental delay, intellectual disability, growth retardation, mild craniofacial abnormalities, cerebral and cerebellar at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Regulation of RNA metabolism has emerged as a critical modulator of neuronal development. We and others recently reported that the RNA stability associated DcpS scavenger decapping enzyme is essential for normal cognitive function (Ahmed I et al 2015; Ng CK et al 2015; Alesi V et al 2018; Masoudi M et al 2020). Here, we demonstrated a functional role for the scavenger decapping activity in determining neuronal development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of RNA metabolism has emerged as a critical modulator of neuronal development. We and others recently reported that the RNA stability associated DcpS scavenger decapping enzyme is essential for normal cognitive function (Ahmed I et al 2015; Ng CK et al 2015; Alesi V et al 2018; Masoudi M et al 2020). Here, we demonstrated a functional role for the scavenger decapping activity in determining neuronal development.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in DcpS can lead to varying motor and developmental delays, and cognitive defects (Ahmed I et al 2015) ranging from mild to more severe phenotypes that also include microcephaly, musculoskeletal and craniofacial abnormalities referred to as Al-Raqad syndrome (ARS) (Ng CK et al 2015; Alesi V et al 2018; Masoudi M et al 2020). This is an intellectual disability disorder identified in four families that harbor mutations in their DcpS gene that negatively impacts decapping activity.…”
Section: Introductionmentioning
confidence: 99%